Book Review: Manisha Priyam, Contested Politics of Educational Reform in India. (December 2018) - Menon, Radhika
Manisha Priyam, Contested Politics of Educational Reform in India . New Delhi: Oxford University Press. 2015. 320 pages. ₹895.